2016
DOI: 10.1016/j.steroids.2016.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Rapid estrogen actions on ion channels: A survey in search for mechanisms

Abstract: A survey of nearly two hundred reports shows that rapid estrogenic actions can be detected across a range of kinds of estrogens, a range of doses, on a wide range of tissue, cell and ion channel types. Striking is the fact that preparations of estrogenic agents that do not permeate the cell membrane almost always mimic the actions of the estrogenic agents that do permeate the membrane. All kinds of estrogens, ranging from natural ones, through receptor modulators, endocrine disruptors, phytoestrogens, agonists… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 183 publications
3
35
0
Order By: Relevance
“…The same laboratory later demonstrated that oestrogen directly interacts with the LTCC protein and inhibits LTCC current even at resting state on cultured HEK293 cells . Indeed, similar observations have been reported for a broad range of ion channels (see review). Research on the rapid non‐genomic roles of oestrogen has been primarily focused on the membranous receptors.…”
Section: Er Activation Signalling Pathways and Cell Functionssupporting
confidence: 62%
“…The same laboratory later demonstrated that oestrogen directly interacts with the LTCC protein and inhibits LTCC current even at resting state on cultured HEK293 cells . Indeed, similar observations have been reported for a broad range of ion channels (see review). Research on the rapid non‐genomic roles of oestrogen has been primarily focused on the membranous receptors.…”
Section: Er Activation Signalling Pathways and Cell Functionssupporting
confidence: 62%
“…These drugs act as estrogen receptor agonists or antagonists, depending on the tissue, and are used for treating breast cancer and osteoporosis [66]. Off-target effects of these drugs are more than likely related to well-known rapid non-genomic actions of estrogen [67]. Indeed, inhibition of both viral entry and TPC activity by submicromolar concentrations of raloxifene is striking.…”
Section: Discussionmentioning
confidence: 99%
“…As we known, the action of 17β‐E2 on different tissues and channel types showed different signaling pathways with dependent or independent of ERα expression (Alvarez‐Baron et al, ; Kow & Pfaff, ; Sarkar et al, ). In this study, the involvement of ERα in 17β‐E2‐activated Cl − currents was supported by several observations.…”
Section: Discussionmentioning
confidence: 99%